Hubungan Motivasi Belajar Dengan Hasil Belajar Sosiologi Bagi Warga Belajar Paket C di PKBM Kadewa Dewa Desa Batu Merah Kecamatan Sirimau Kota Ambon - Ersa E. Manafwayak; L. J. Lokollo; R. Tutupary (Peneliti.net, 2023)
This study aims to determine the relationship between learning motivation and sociology learning outcomes for Package C learning residents at PKBM KADEWA DEWA, Batu Merah Village, Sirimau District, Ambon City. The type of research used in this research is correlational research which aims to improve learning in the classroom. The results of the descriptive analysis of the data show that residents learning PKBM Kadewa Dewa Desa Batu Merah, Sirimau District, Ambon City have good results, this is related to good learning motivation. using the product moment correlation formula